Writing the Dandy through Art Criticism: Elegance and Civilization in Monsieur, 1920–1924. (26th May 2016) - Potvin, John
Abstract: The French monthly Monsieur had a rather short lifespan (1920–1924), but it nevertheless managed to outline a " retour à l'ordre " for the dandy in part through its art critical writing. Monsieur's critical writing provided a unique space for an empathetic entry (or Einfühlung ) into the works of art, which in turn aided the perpetuation of a postwar dandyist masculinity.